Comparative evaluation of the use of dental plugger with diff erent forms of the working surface in a mathematical model and experiment (Эндодонтия Today)
The study analyzed the capabilities of existing dental plugger in the virtual model of the process seals the fi lling material and its adaptation to the cavity walls. Programmed in ANSYS SpaceClaim tools infl uence on the fi lling material with suffi cient force to promote the latest by 1 mm. In a study in the same way the data has been processed we developed a funnel-shaped plugger. According to the results of a mathematical model, conclusions were drawn about the theoretical superiority of our tool over existing analogues. This conclusion was confi rmed in a laboratory experiment for the real work surfaces exposed dental plugger for fi lling material under standard conditions.